EDDY CURRENTS IN LAMINATED RECTANGULAR CORES - Mukerji, Saurabh Kumar; George, Moleykutty; Ramamurthy, M. B.; Asaduzzaman, Khandaker (E M W PUBLISHING, 2008)
A simplified expression for the eddy current loss in laminated rectangular core is obtained using linear electromagnetic field analysis. The treatment takes cognizance of current interruption phenomena, by considering capacitive effects of insulation regions. Analysis presented in this paper assumes identical field distribution in each lamination and ignores eddy currents in insulation regions.